2022
DOI: 10.3389/fmed.2022.980110
|View full text |Cite
|
Sign up to set email alerts
|

Presbyopia-correcting performance and subjective outcomes of a trifocal intraocular lens in eyes with different axial lengths: A prospective cohort study

Abstract: PurposeTo compare the presbyopia-correcting performance, visual quality, satisfaction and life quality after implantation of a diffractive trifocal intraocular lens (IOL) in eyes with different axial lengths (AL).MethodsThis prospective cohort study enrolled patients with implantation of a trifocal IOL. Manifest refraction, uncorrected and distance-corrected visual acuity at different distances, contrast sensitivity, aberrations and IOL decentration were measured 3 months after surgery. Spectacle independence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Among these patients, CTRs were applied cataract patients in long AL group to set up a relatively fair evaluation criteria, reduce the hyperopic shift that is most likely to occur in patients with long AL and make the results more objective and reliable. The research shows no difference in the postoperative SE value of the two groups, which is basically consistent with the results of previous studies [8,14,26] . The desire of most cataract patients with AHM is to no longer depend on spectacles after surgery, which improves quality of life and enhances selfconfidence.…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringssupporting
confidence: 92%
See 1 more Smart Citation
“…Among these patients, CTRs were applied cataract patients in long AL group to set up a relatively fair evaluation criteria, reduce the hyperopic shift that is most likely to occur in patients with long AL and make the results more objective and reliable. The research shows no difference in the postoperative SE value of the two groups, which is basically consistent with the results of previous studies [8,14,26] . The desire of most cataract patients with AHM is to no longer depend on spectacles after surgery, which improves quality of life and enhances selfconfidence.…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringssupporting
confidence: 92%
“…Among them, trefoil aberration which cannot be corrected, accounts for a large proportion of the overall HOA, which corresponds to the incidence of starburst, and this phenomenon existed in the two groups. An prospective cohort study, Sun et al [26] observed that there were no significant differences in the coma aberration, spherical aberration and trefoil aberration among eyes with different ALs, and the proportion of trefoil aberration was also larger than other aberrations from 0.23 μm to 0.25 μm. While Meng et al [27] found there was the greater intraocular HOAs and coma aberration in the extreme myopia group (AL>28 mm).…”
Section: Effectivity and Safety Of Intraocular Lenses And Tension Ringsmentioning
confidence: 98%
“…Sun [ 19 ] and Steinwender [ 14 ] emphasized the superior corrected distance visual acuity achieved with the diffractive trifocal IOL. Sun et al [ 20 ] reported that trifocal IOL offered stable and satisfactory visual outcomes for eyes with long AL. Thus, our research confirmed that the macular function of patients appeared not to be defective.…”
Section: Discussionmentioning
confidence: 99%
“…Introduced by NASA in 2010, the term ‘digital twin’ was intended to represent a comprehensive simulation of the human during space travel from shuttle launch to outer space and return to Earth. 45,46 This capability relies on computational modeling, real-time measurement or sensing, and AI-enabled processing of data that can adapt to changes within these data over time. Similarly, creating a digital twin using PROMs and other forms of patient-generated health data can afford opportunities for decision making and management throughout an episode of care.…”
Section: The Role Of Technology In Patient-reported Outcome Measureme...mentioning
confidence: 99%